Characterization on the Properties of Jute Fiber at Different Portions. (26th October 2015) - Shahinur, Sweety; Hasan, Mahbub; Ahsan, Qumrul; Saha, Dilip Kumar; Islam, Md. Saiful
Abstract : Natural fibers are environment-friendly, biodegradable, nonabrasive, and less costly and exhibit high initial modulus and high moisture absorption. However, they have nonuniformity in their mechanical, physical, chemical, and thermal properties at different portions. For this reason, long jute fiber was cut into three different portions and subsequently characterized using single fiber tensile test, differential scanning calorimetric, thermogravimetric analysis, X-ray diffraction, and scanning electron microscopy according to top, middle, and cutting portions. The crystallinity and moisture content were measured by XRD data and moisture absorption test of the different portions of the raw jute fiber, respectively. The middle portion had better mechanical, thermal, chemical, and crystalline properties compared to the other two portions of the jute fiber. The diameter gradually became thinner from cutting to top portions. Thus the middle portion of jute fiber would be the better choice while being used as reinforcement in composites.